BOSHLANG’ICH SINF TEXNOLOGIYA TA’LIMI DARSLARINING SAMARADORLIGINI OSHIRISHGA INNOVATSION YONDASHISH - Sanakulov, X.R.; Sanakulova, A.R. (SCIENCE and SOCIETY, 2019)
The article provides guidelines and methodical recommendations for primary school students at the labor classes.